(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Тhis article raises questions of interaction between state and religion; regulate their activities, on the regulation of interaction between state and religion, their past, present and future is explored. Also, In this article the main results of Kazakhstan`s Chairmanship at the Organization of Islamic Cooperation are analyzed in brief. The chairmanship of at the OIC is very important event in the history of Kazakhstani diplomacy. Kazakhstan as a former chairman of OIC now possesses extra diplomatic mechanisms of influencing on the international issues, particularly on those concerning Muslim world. This chairmanship, undoubtedly, meets long-term national interests of Kazakhstan. Kazakhstan`s chairmanship at the OIC insures strategic opportunity and enforces its position in the region. Surely, this fact can be named as the biggest historic and diplomatic achievement of our nation during the last century. Keywords: Religion, theocratic, policy, state, Kazakhstan, Europe, OIC, modernism, diplomacy, stability.